A cross-sectional study on the level of knowledge, attitude and practice among parents of children aged 18 years old and below on refractive errors in Rumah Juntan, Sibu from 26th October to 31st December 2009 - Akad Alkaff, b Yahya; Asma Zafirah, bt Aizan; Asyilah, bt Mohamad West; Xien, Lee Jing; Ren, Ling Shar; Marfiza, bt Aluwie; Nurul Fatiha, bt Azman; Nur Suhana, bt Zainal Adzman; Lin, Pang Jia; Boon, San Chyi; Surenthiran, a/l Ramanathan; Siti Hajar, Rosli; et al. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
A cross sectional research on the assessment of level of knowledge, attitude, and practice on refractive errors among 80 parents with children ages 18 years old and belowin Rumah Juntan, Sibu was carried out from 26th October to 31st December 2009.